The Urgency to Regulate Pricing for Two-Wheels Online Ride Hailing Platform: Who Benefits the Most? Who Needs it the Most? - Adilla Meytiara (PT Publikasiku Academic Solution, 2024)
The rapid expansion of two-wheeler ride-hailing platforms has transformed urban mobility, offering convenience and cost-effectiveness. However, the unregulated pricing strategies of these services pose challenges for both consumers and drivers. This study explores the urgency to implement pricing regulations and identifies the primary beneficiaries and those in need of such measures. Through a comprehensive review of existing literature, stakeholder interviews, and market analysis, it becomes evident that price regulation can stabilize fares, ensuring affordability for riders while providing fair compensation for drivers. Riders, particularly from low and middle-income groups, benefit most from regulated pricing as it guarantees predictable and reasonable fares, enhancing their access to reliable transportation. Drivers, often facing income volatility due to fluctuating ride demand and pricing schemes, also stand to gain significantly from a regulated system that ensures fair wages and job security. Furthermore, regulatory frameworks can foster competitive equity among ride-hailing companies, preventing monopolistic practices and encouraging healthy market competition. Therefore, the regulation of pricing for two-wheeler ride-hailing platforms is crucial not only for consumer protection but also for safeguarding driver welfare and promoting a balanced market ecosystem. The findings advocate for policymakers to urgently address this regulatory gap, ensuring that the benefits of ride-hailing services are equitably distributed across all stakeholders.